Diagnosis of gestational diabetes (GDM) by the IADPSG (international association of diabetes and pregnancy study groups) criteria: potential to improve pregnancy outcomes. (18th April 2012) - Ghosh, M; Pankaja, S; Dawidziak, M; Viswanath, A; Churchill, D
Abstract : The IADSPG criteria1 will increase the prevalence of GDM with implications on resources. We studied the impact of the IADPSG criteria on the prevalence and pregnancy outcomes in GDM. Method: All women undergoing antenatal 2 hr 75gm OGTT between 2001and 2010 were selected for the study. We reviewed the pregnancy outcomes in 975 women diagnosed with GDM. Out of 975 women with GDM, 474 women were identified by both criteria, 187 women were identified by WHO criteria only and 314 women were identified by IADPSG criteria only. Results: The following table shows the comparison of the pregnancy outcomes between the above 3 groups. Discussion: Incidence of macrosomia (P< 0.001) and neonatal admissions (P<0.01) are significantly higher in IADPSG group. Timely interventions in women missed by the WHO criteria (currently not treated) will reduce the adverse outcomes. The results are similar to the studies from Ireland2 and Italy. Conclusion: Although implementation of the IADPSG criteria will increase the prevalence, it will prove to be cost-effective in long term by reducing perinatal morbidities.